The Serpent Column : a cultural biography - Stephenson, Paul (Onassis series in Hellenic culture, 2016)
Paul Stephenson twists together multiple strands to relate the cultural biography of a unique monument, the Serpent Column, which stands today in Istanbul 2500 years after it was raised at Delphi